Neurodegenerative Disease Diagnosis via Ion‐Level Detection in the Brain. Issue 8 (21st May 2021) - Chen, Ying; Wei, Min; Lee, Jiyoung; Zhao, Jing; Lin, Peihua; Wang, Qiyue; Li, Fangyuan; Ling, Daishun
Abstract : Metal ions are heavily involved in the membrane potential and intracellular activities of cells. Increasing evidences have shown that it is critical to evaluate the ion levels and monitor their dynamic changes in the brain for the diagnosis of neurodegenerative diseases (NDDs), including Alzheimer's disease, Parkinson's disease, Huntington disease, amyotrophic lateral sclerosis, and so on. Herein, the roles of metal ions in the occurrence and development of NDDs are intensively discussed, and the recent advances in probes and sensors for ion‐level detection are summarized. Finally, the further applications of ingenious ion‐selective probes and sensors are outlined, highlighting the future opportunities for the metal ion‐based diagnosis of NDDs. Abstract : Metal ions are highly associated with the development of neurodegenerative diseases (NDDs). It is promising to diagnose NDDs via ion‐level detection. Herein, the roles of ions in the occurrence and development of NDDs as well as the recent advances of ion‐level detection are summarized. And the future opportunities for ion‐based diagnosis of NDDs are highlighted.